Time-Domain Characterization of Dual Band Spiral Antenna with WMTS/UWB Application - Saira Joseph; Sunil Jacob; Binu Paul; Shanta Mridula; Pezholil Mohanan (International Journal of Antennas and Propagation)
A coplanar waveguide- (CPW-) fed spiral antenna with dual band application is presented. The antenna is designed to operate over the UWB (3.1–10.6 GHz) band as well as in a lower band suitable for WMTS (1.395–1.4 GHz). Frequency domain characterization shows that the antenna is well matched with appreciable gain in both bands. Time-domain studies are carried out to check the suitability of the antenna in pulsed communication. A prototype of the antenna is fabricated and measured results show low group delay variation in the UWB. FWHM and ringing of antenna impulse response, fidelity factor, and radiated power spectral density are also presented.